Routine COVID-19 testing may not be necessary for most cancer patients - Ali Motlagh (Nature Portfolio, 2021)
Abstract Cancer patients are at risk for severe complications or death from COVID-19 infection. Therefore, the need for routine COVID-19 testing in this population was evaluated. Between 1st August and 30th October 2020, 150 cancer patients were included. Symptoms of COVID-19 infection were evaluated. All eligible individuals went through RT-PCR and serological tests for COVID-19. At the same time, 920 non-cancer patients were recruited from a random sample of individuals who were subject to routine molecular and anti-body screening tests. Of 150 cancer patients, 7 (4.7%) were RT-PCR positive. Comorbidity made a significant difference in the RT-PCR positivity of cancer patients, 71.4% positive versus 25.8% negative (P-value = 0.02). The average age for negative and positive groups was 53.3 and 58.2 respectively (P-value = 0.01). No significant difference was observed between cancer and non-cancer patients regarding COVID-19 antibody tests. However, cancer patients were 3 times less likely to have a positive RT-PCR test result OR = 0.33 (CI: 0.15–0.73). The probability of cancer patients having a positive routine test was significantly lower than non-cancer patients, and the concept that all cancer patients should be routinely tested for COVID-19 may be incorrect. Nevertheless, there may be a subgroup of patients with comorbidities or older age who may benefit from routine COVID-19 testing. Importantly, these results could not be subjected to multivariate analysis.